Thermal decomposition of palladium(II) pyrazolyl complexes. Part I - Netto, AVG; Takahashi, P. M.; Frem, RCG; Mauro, Antonio Eduardo [UNESP]; Zorel, H. E. (Elsevier B.V., 2004)
The thermal behavior of simple and mixed pyrazolyl complexes [PdCl2(phmPz)(2)] (1),[Pd(N-3)(2)(phmPz)(2)] (2), [Pd(SCN)(2)(phmPz)(2)] (3), and [Pd(N-3)(SCN)(phmPz)(2)] (4) (phmPz: 1-phenyl-3-methylpyrazole) has been investigated by means of thermogravimetry (TG) and differential thermal analysis (DTA). From the initial decomposition temperatures, the thermal stability of the complexes can be ordered in the sequence: 4 < 2 < 3 < 1. The final products of the thermal decompositions were characterized as metallic palladium (Pd-0). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: palladium; pyrazoles; IR and NMR spectroscopy; thermal analysis